2021
DOI: 10.1093/plcell/koaa055
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for phloem loading via the abaxial bundle sheath cells in maize leaves

Abstract: Leaves are asymmetric, with different functions for adaxial and abaxial tissue. The bundle sheath (BS) of C3 barley (Hordeum vulgare) is dorsoventrally differentiated into three types of cells: adaxial structural, lateral S-type, and abaxial L-type BS cells. Based on plasmodesmatal connections between S-type cells and mestome sheath (parenchymatous cell layer below bundle sheath), S-type cells likely transfer assimilates towards the phloem. Here, we used single-cell RNA sequencing to investigate BS differentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 56 publications
3
79
0
Order By: Relevance
“…Not only do bundle sheath cells of C 4 plants undertake a key role in photosynthesis, but they are also the primary location of starch synthesis (Lunn and Furbank, 1997) and sulphur metabolism (Burgener et al , 1998; Burnell, 1984; Gerwick et al , 1980; Passera and Ghisi, 1982; Schmutz and Brunold, 1984). Distinct classes of bundle sheath cells have been reported in Zea mays (maize), with abaxial bundle sheath cells of rank‐2 intermediate veins being specialized for phloem loading (Bezrutczyk et al , 2021). The importance of bundle sheath cells in the C 4 leaf, and the discovery that their thickened cell walls allow them to be separated from the rest of the leaf, led to them being studied intensively.…”
Section: Introductionmentioning
confidence: 99%
“…Not only do bundle sheath cells of C 4 plants undertake a key role in photosynthesis, but they are also the primary location of starch synthesis (Lunn and Furbank, 1997) and sulphur metabolism (Burgener et al , 1998; Burnell, 1984; Gerwick et al , 1980; Passera and Ghisi, 1982; Schmutz and Brunold, 1984). Distinct classes of bundle sheath cells have been reported in Zea mays (maize), with abaxial bundle sheath cells of rank‐2 intermediate veins being specialized for phloem loading (Bezrutczyk et al , 2021). The importance of bundle sheath cells in the C 4 leaf, and the discovery that their thickened cell walls allow them to be separated from the rest of the leaf, led to them being studied intensively.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from plant roots, there is growing interest in using scRNAseq technologies to profile the development of other important plant tissues, including leaf 21,22 , flower 23 , pollen and sperm 24 , and seed endosperm 25 . Single-cell RNA-seq has also moved beyond Arabidopsis, with studies emerging for tomato 26 , rice 27 , maize [28][29][30][31] , and moss 32 . Beyond single-cell RNA-seq, epigenomic profiling afforded by single-cell ATAC-seq has become increasingly used in plants [33][34][35] and is ideally suited to explore gene regulation, elucidate regulatory networks, and even more finely classify cell types.…”
Section: The Technologiesmentioning
confidence: 99%
“…Also, Zea mays, being a representative of C4photosynthetic cereals, is a promising object for SC experiments due to the large size its cells, which allows to easily isolate specific cells, for example, from the shoot apical meristem. To date, there are studies based on the single-cell analysis for corn tissues carried out on a shoot apex (Satterlee et al, 2020), phloem (Bezrutczyk et al, 2021), and ears (Xu et al, 2021). The first and so far only scRNA-seq on rice roots (Liu et al, 2021) revealed significant differences in the characteristics of individual cell types in comparison to the cell types of A. thaliana, which indicates the presence of significant species-specific differences at the cellular level.…”
Section: Existing Approaches To the Analysis Of Single-cell Data And Their Potential For Cell-based Modelsmentioning
confidence: 99%